1998
DOI: 10.1002/(sici)1096-8628(19980526)77:4<268::aid-ajmg3>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct duplication of 9p22→p24 in a child with duplication 9p syndrome

Abstract: A de novo direct duplication of 9p22-->p24 was shown in a child with a duplication 9p phenotype by GTG banding and fluorescence in situ hybridization (FISH) using a chromosome-9 specific painting probe as well as 6 YAC DNA probes localized to the 9p13-9p23 region. The breakpoints in this patient and previously reported patients suggest that 9p22 may be the critical region for duplication 9p syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 8 publications
(13 reference statements)
0
33
0
2
Order By: Relevance
“…Facial and hand anomalies are found in a case with trisomy 9p21‐p24 (13,14). Duplication of 9p22‐p24 (15) and direct duplication of 9p22‐p24 (16) are present in patients with trisomy 9p syndrome. A patient with a ring chromosome with an inverted 9p22.3‐p24.3 duplication showed some trisomy 9p features (17).…”
Section: Discussionmentioning
confidence: 99%
“…Facial and hand anomalies are found in a case with trisomy 9p21‐p24 (13,14). Duplication of 9p22‐p24 (15) and direct duplication of 9p22‐p24 (16) are present in patients with trisomy 9p syndrome. A patient with a ring chromosome with an inverted 9p22.3‐p24.3 duplication showed some trisomy 9p features (17).…”
Section: Discussionmentioning
confidence: 99%
“…Notably the characteristic facial appearance of this syndrome, resulting from downturned mouth, bulbous nose, short philtrum, hypertelorism and downward slanting palpebral ®ssures, was not present. According to Haddad et al [2] and Fujimoto et al [1] the dysmorphic features in 9p duplications are mainly due to the trisomy of band p22. In our case 9p22 duplication was limited to sub-band 22.3 and the absence of the typical dup 9p22 phenotype indicated that this could be ascribed to sub-bands p22.1 and p22.2.…”
Section: Discussionmentioning
confidence: 99%
“…Duplication 9p leads to a clinically recognisable syndrome in which involvement of band p22 seems to have a predominant role [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Fujimoto et al [1998] reported a de novo duplication of 9p22p24 and reviewed eight cases including an isolated de novo duplication 9p. The common clinical findings in these patients include mental retardation, small stature, microcephaly, downward‐slanting palpebral fissures, deep‐set eyes, hypertelorism, globular or prominent nose, downturned mouth, prominent, simple, and apparently low‐set ears, single palmar crease, and phalangeal hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by severe pre‐ and postnatal growth retardation, severe developmental and mental retardation, distinct facial appearance, and variable internal and external anomalies. WHS is typically associated with a deletion of the short arm of chromosome 4, particularly 4p16.3, that can be a result of a terminal or interstitial deletion, translocation, or a ring chromosome 4 [Fraisse et al, 1977; Estabrooks et al, 1994; Chen et al, 1998].…”
Section: Introductionmentioning
confidence: 99%